Updates on Behavioural Interventions for Smoking Cessation: A Systematic Review of Systematic Reviews - Nur Syuhada Abqari Luthfi Albert; 'Atifah Najib Badri Najib; Nurain Afiqah Mohd Aznan; Mohamad Haniki Nik Mohamed; Syahrir Zaini (IIUM Press, International Islamic University Malaysia, 2024)
In Malaysia, tobacco smoking is considered to be one of the leading causes of early and preventable mortality. The 'Clinical Practice Guidelines on Treatment of Tobacco Use Disorder 2016' is utilised to provide safe and effective smoking cessation services for smokers to quit successfully. Since the launch of the 2016 CPG, there have been several new pieces of evidence regarding behavioural interventions for tobacco smoking cessation with various outcomes. Therefore, the guidelines are expected to be updated to assist healthcare providers in helping smokers quit smoking. This study aims to review the evidence from 2016 onwards for behavioural interventions in smoking cessation reported from published systematic reviews, and to update the CPG on tobacco use disorder by conducting a systematic review of systematic reviews methodology. The Cochrane Library, PubMed, and Scopus databases were used to conduct a comprehensive literature search. Two reviewers performed the screening and study selection, with disagreements resolved by consensus or the involvement of another reviewer. Quality assessment and data extraction are performed by one reviewer and checked by another. AMSTAR-2 tool was used to perform the risk of bias assessment. A narrative synthesis of the data extracted was provided. The searches resulted in a total of 276 articles and out of these, 23 systematic reviews were included. The included studies incorporated various smoking cessation interventions. Smokers of all ages and a small proportion of recent quitters are involved. They may be from the general or the special population. 14 reviews were rated as high quality, 2 were moderate, 4 were low and 3 were critically low by the AMSTAR-2 tool. The analysis found that counselling sessions, online interventions, self-help materials and motivational interviewing may increase cessation rates in the long term, if not, short term. Counselling sessions demonstrate the strongest evidence of benefit in smokers trying to quit. Findings that can be added to the updated CPG include app-based, incentives, feedback on spirometry results, exercise and behavioural interventions for people living with HIV and AIDS, COPD patients, and underprivileged older smokers.